HLA and TCR Recognition of Medications in Severe Cutaneous Adverse Reactions - Pan, Ren-You; Wu, Yi-Chih; Chung, Wen-Hung; Hung, Shuen-Iu (Current Immunology Reviews (Discontinued), 2014)
Severe cutaneous adverse reactions (SCAR) include drug reaction with eosinophilia and systemic symptoms (DRESS), Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN). Although rare, SCAR has significant public health impact because of the unpredictability, high mortality and morbidity. The common culprit drugs for SCAR include aromatic antiepileptics (e.g., carbamazepine, phenytoin, lamotrigine, phenobarbital), antibiotics (e.g., sulfamethoxazole, sulfonamides, abacavir, nevirapine, dapsone), NSAIDs, and allopurinol, etc. Increasing studies revealed the strong genetic association between HLA alleles and SCAR. To explain how the interactions of a small chemical compound (drug/metabolite), HLA, TCR, and peptides induce the destructive T cell response in SCAR, three theories are proposed: the “hapten/prohapten” theory, the “pharmacological interaction with immune receptors” (p-i) concept, and the “altered peptide repertoire” model. In this article, we summarize important studies on the immunogenetic association between HLA and SCAR, review the molecular interaction of HLA/TCR/drug/peptide antigens, and discuss the potential pathological mechanistic models of HLA and TCR recognition of medications in SCAR. The accumulated knowledge will help to develop safer drugs, and thus facilitate preclinical immunotoxicity screening. Upon gaining insights into the molecular interaction in the immune synapse composing of the HLA/drug/peptide/TCR, we will advance our understandings to the pathogenesis of the SCAR, and a better strategy may be offered to avoid the occurrence, or improve the treatment of SCAR.
Keywords: human leukocyte antigens